The Influence of Training and Human Resource Development in the Context of Improving Work Morale and Employee Performance in Mas Medal Ikat Weaving MSMEs Bandar Kidul Kediri - Wahyudiono, Muji; Ratnanto, Sigit (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aims: This research investigates the effects of human resource development and training on employee performance and morale, seeking to measure the degree to which these two independent variables contribute to the outcomes can increase employee motivation and productivity in the organization. Design/Methode/Approach :: this study employs a quantitative causal research approach. Data were gathered using a questionnaire filled out by 30 respondents. To assess the impact of human resource development, multiple linear regression analysis was conducted, training, employee performance and work morale. Research findings: demonstrate that training exerts a positive and substantial impact on both employee performance and work morale. Additionally, the development of human resources significantly affects these two dependent variables. Overall, HR training and development explains 62% of the variability in employee performance and morale. The following research strengthens previous literature regarding the importance of training and human resource development in increasing work motivation and productivity. These findings provide additional empirical evidence of a positive relationship between these variables. Companies are advised to continue to improve the quality of HR training and development programs by ensuring the relevance of the material, support from superiors, and adequate facilities. This can help create a more competent and motivated workforce. Implications for practitioners/policy: This research is limited to a relatively small sample size and includes only one company. Further research can be carried out more widely to increase the generalizability of the results.